Respiratory morbidity in susceptible populations: the role of joint exposure to multiple environmental chemicals and pollutants - Benka-Coker, Wande, author; Magzamen, Sheryl, advisor; Peel, Jennifer, committee member; Wilson, Ander, committee member; Anderson, Brooke, committee member (Colorado State University. Libraries, 2019)
Exposure to ambient pollution from environmental chemicals and pollutants has been associated with a range of adverse respiratory outcomes; susceptible populations are disproportionately affected. Children with asthma are particularly at risk for adverse respiratory effects of environmental agents. The recent increase in US and worldwide pediatric asthma prevalence has encouraged new lines of inquiry focusing on environmental factors, rather than genetic factors, as the main etiologic agent in asthma-related morbidity; the complex relationship between individuals and their environment requires improved characterization and quantification.

The study of potential joint effects from multiple environmental chemical stressors is particularly relevant for chronic diseases with strong environmental antecedents, including asthma. As children with asthma tend to have spatially and temporally heterogeneous exposure to multiple domains of environmental chemicals determined by regional characteristics, study approaches with an understanding of the complexities of exposure (i.e. exposure data that are high dimensional and strongly correlated) of the health impact of multiple pollutants are required.

In this dissertation, we sought to evaluate the association between multipollutant exposures to ambient environmental chemicals and pollutants (ECP) and respiratory morbidity in uniquely exposed populations. By implementing health risk-based multipollutant epidemiologic approaches, we targeted potential synergistic effects within multiple domains of ambient ECP, with specific attention to criteria air pollutants and agricultural pesticides.

Chapter 1 describes background information relevant to the dissertation while providing context for the multipollutant approaches and highlighting the specific objectives; Chapters 2 – 4 summarize methodology, study findings and aim-specific discussion; and the final chapter provides a discussion of overall findings, strengths, limitations, and suggestions for future research.